Intranasal Dexmedetomidine Reduces Postoperative Opioid Requirement in Patients Undergoing Total Knee Arthroplasty Under General Anesthesia - Seppänen Suvi-Maria; Kuuskoski Ronja; Mäkelä Keijo; Saari Teijo; Uusalo Panu (United States, 2025)
Background: Total knee arthroplasty (TKA) causes severe pain, and strong opioids are commonly used in postoperative analgesia. Dexmedetomidine is a novel alpha-2-adrenoceptor-activating drug indicated for procedural sedation, but previous studies have shown clinically relevant analgesic and antiemetic effects. We evaluated retrospectively the effect of intranasal dexmedetomidine on the postoperative opioid requirement in patients undergoing TKA.
Methods: One hundred and fifty patients with ASA status 1-2, age between 35 and 80 years, and scheduled for unilateral primary TKA under total intravenous anesthesia were included in the study. Half of the patients received 100 μg of intranasal dexmedetomidine after anesthesia induction, while the rest were treated conventionally. The postoperative opioid requirement was calculated as morphine equivalent doses for both groups. The effect of dexmedetomidine on postoperative hemodynamics, length of stay (LOS), and incidence of postoperative nausea and vomiting (PONV), was evaluated.
Results: The cumulative postoperative opioid consumption was significantly reduced in the dexmedetomidine group compared to the control group (-28.5 mg, 95% CI 12-47 mg P < .001). The reduction in cumulative opioid dose was significantly different between the groups already at 2, 12, 24, and 36 h postoperatively (P < .001). LOS was shorter in the dexmedetomidine group (P < .001), and the dexmedetomidine group had lower postoperative mean arterial pressure and heart rates were lower compared to the control group (P < .001). The incidence of PONV did not differ between the groups (P = .64).
Conclusion: Intraoperatively administered intranasal dexmedetomidine reduces postoperative opioid consumption and may be associated with a shorter hospital stay in patients undergoing TKA under general anesthesia.